Boron adsorption in lowland soils from southern of the State of Minas Gerais, Brazil - Azevedo, Watson Rogério de; Faquin, Valdemar; Fernandes, Luiz Arnaldo (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this study was to evaluate the B adsorption capacity in four lowland soils from Lavras, MG, Brazil, through Langmuir and Freundlich isotherm parameters. This study was conducted throughout October and November, 1998. Samples of Alluvial Soil, Low-Humic Gley, Humic Gley and artificially drained Bog Soil were collected in 0-20 cm of profundity and sieved to 2 mm. Samples with or without liming application were incubated during 30 days. Duplicates of 4.0 g soil samples, conditioned in polyethylene tubes, received eight doses of B (0, 2, 4, 8, 12, 16, 24 and 32 mg mL-1) prepared with 20 mL CaCl2.2H2O 0.01 mol L-1 solution, using boric acid. The amount of B in the balance solution was measured through the Azomethine-H method. The high organic matter content in Humic Gley soil provided higher B adsorption capacity. The adsorption was highly correlated with organic matter, specific surface area, kaolinite, and exchangeable aluminum. Lime application provided decrease in B adsorption capacity for all soils.